Depiction of Lord Indra on the southern wall of Shiva Temple 1 - Temples of India Project Team (Jio Institute, 2024)
Indra, the guardian deity of the east, is carved on the east face of the southern wall of Shiva Temple 1. He is depicted with two arms and shown holding a vajra (thunderbolt weapon associated with Indra) in his left hand and his right hand is placed on his thigh. His vahana (mount) Airavat is also shown on his left at the bottom.